Correction: Breaking of the Bancroft rule for multiple emulsions stabilized by a single stimulable polymer. Issue 5 (12th January 2015) - Besnard, L.; Protat, M.; Malloggi, F.; Daillant, J.; Cousin, F.; Pantoustier, N.; Guenoun, P.; Perrin, P.
Abstract : Correction for 'Breaking of the Bancroft rule for multiple emulsions stabilized by a single stimulable polymer' by L. Besnard et al., Soft Matter, 2014, 10, 7073–7087.